Interactive Effects of Dopamine Baseline Levels and Cycle Phase on Executive Functions: The Role of Progesterone - Hidalgo-Lopez, Esmeralda; Pletzer, Belinda (Frontiers in Neuroscience, 2017)
Estradiol and progesterone levels vary along the menstrual cycle and have multiple neuroactive effects, including on the dopaminergic system. Dopamine relates to executive functions in an ‘inverted U-shaped’ manner and its levels are increased by estradiol. Accordingly, dopamine dependent changes in executive functions along the menstrual cycle have been previously studied in the pre-ovulatory phase, when estradiol levels peak. Specifically it has been demonstrated that working memory is enhanced during the pre-ovulatory phase in women with low dopamine baseline levels, but impaired in women with high dopamine baseline levels. However, the role of progesterone, which peaks in the luteal cycle phase, has not been taken into account previously. Therefore, the main goals of the present study were to extend these findings (i) to the luteal cycle phase and (ii) to other executive functions. Furthermore, the usefulness of the eye blink rate (EBR) as an indicator of dopamine baseline levels in menstrual cycle research was explored. 36 naturally cycling women were tested during three cycle phases (menses – low sex hormones; pre-ovulatory – high estradiol; luteal – high progesterone and estradiol). During each session, women performed a verbal N-back task, as measure of working memory, and a single trial version of the Stroop task, as measure of response inhibition and cognitive flexibility. Hormone levels were assessed from saliva samples and spontaneous eye blink rate was recorded during menses. In the N-back task, women were faster during the luteal phase the higher their progesterone levels, irrespective of their dopamine baseline levels. In the Stroop task, we found a dopamine-cycle interaction, which was also driven by the luteal phase and progesterone levels. For women with higher EBR performance decreased during the luteal phase, whereas for women with lower EBR performance improved during the luteal phase. These findings suggest an important role of progesterone in modulating dopamine-cycle interactions. Additionally, we identified the eye blink rate as a non-invasive indicator of baseline dopamine function in menstrual cycle research.